2015
DOI: 10.18632/oncotarget.13513
|View full text |Cite
|
Sign up to set email alerts
|

Tag SNPs of long non-coding RNA TINCR affect the genetic susceptibility to gastric cancer in a Chinese population

Abstract: Tissue differentiation-inducing non-protein coding RNA (TINCR) is required for normal epidermal differentiation. TINCR is also strongly overexpressed in human gastric cancer (GC) and contributes to carcinogenesis and tumor progression. However, the association between TINCR polymorphisms and the risk of any diseases, such as GC, remains unknown. In the present study, the tag single nucleotide polymorphisms rs8113645, rs2288947, rs8105637, and rs12610531 were analyzed in 602 patients with GC and 602 age- and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Although TINCR is strongly upregulated in GC and could promote cell growth,15,16 the specific mechanism that was involved in human GC progression still needed to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Although TINCR is strongly upregulated in GC and could promote cell growth,15,16 the specific mechanism that was involved in human GC progression still needed to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, studies have confirmed that the lncRNA TINCR gene, which regulates cell invasion and migration, is associated with susceptibility to various diseases. A study by Ma et al found that SNPs of the lncRNA TINCR were significantly associated with decreased gastric cancer susceptibility by decreasing its gene expression levels. Moreover, a study by Zheng et al found that lncRNA TINCR polymorphisms were associated with the progression of colorectal cancer, and SNP rs2288947 may be a biomarker with the occurrence and progression of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Recently, studies have found that genetic variation in TINCR was associated with a variety of diseases, such as the SNP rs2288947, which contributed to the susceptibility and progression of colorectal cancer and susceptibility to gastric cancer. 19,20 Furthermore, studies have found that some genes that regulate cell proliferation, invasion, and migration are associated with susceptibility to miscarriage; for example, H19 and p53 gene polymorphisms. 8,21 These studies suggest that TINCR gene polymorphisms may be associated with recurrent miscarriage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected relevant information, such as age, gender, hypertension, diabetes, smoking history, drinking history, residence, family history of GC (FH), and clinical data from the medical history, or face-to-face interviews were conducted to supplement the above information. The definitions of hypertension and diabetes were described in the previous studies [ 5 , 6 ]. The smokers were defined as individuals who formerly or currently smoked ≥10 cigarettes per day no less than 2 years.…”
Section: Methodsmentioning
confidence: 99%